Outbreak of invasive pneumococcal disease among shipyard workers, Turku, Finland, May to November 2019 - Marius Linkevicius; Veronica Cristea; Lotta Siira; Henna Mäkelä; Marjaana Pitkäpaasi; Timothee Dub; Hanna Nohynek; Taneli Puumalainen; Esa Rintala; Merja E. Laaksonen; Thijs Feuth; Juha O. Grönroos; et al. (Publications Office, 2025)
We report an outbreak of invasive pneumococcal disease and pneumococcal pneumonia among shipyard workers, in Turku, Southwest Finland. In total, 31 confirmed and six probable cases were identified between 3 May and 28 November 2019. Streptococcus pneumoniae serotypes 12F, 4 and 8 were isolated from blood cultures of 25 cases. Occupational hygiene measures and vaccination of ca 4,000 workers are underway to control the outbreak at the shipyard.